Effect of post warm-up resting interval on static and dynamic balance, and maximal muscle strength followed by the FIFA 11+ and dynamic warm-up exercises - Chen, Y. S.; Lai, W. L.; Hou, C. W.; Chen, C. H.; Chiu, Y. W.; Bezzera, P. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: It has been reported that implementation of the FIFA11+ can immediately increase exercise performance. However, the elapsed time of post warm-up (WU) effect of the FIFA 11+ is unclear. METHODS: Twenty-one male university football players were randomly assigned into the FIFA 11+ (N.=10) or control group (conventional dynamic WU exercise, N.=11). The participants performed static, drop jump, and maximal voluntary muscle contraction (MVC) tests before and after the WU protocol in four different occasions with 0, 10, 20 or 30 min resting interval. Static balance with 4 sensory conditions (stable surface with eyes open, stable surface with eyes closed, unstable surface with eyes open, and unstable surface with eyes closed), drop jump (30 and 50 cm heights), and MVC of knee extension and flexion were examined. The electromyography (EMG) of rectus femoris, vastus medialis, biceps femoris were recorded during the drop jump and MVC measurements. The percentage of pre-and-post WU changes were used for comparison. RESULTS: The MVC slightly decrease immediate after the FIFA11+ but slightly increase after 10, 20, and 30 min resting interval. However, there was no significant difference in all variables during static and dynamic balance measurements and the EMG measurements. No between-group differences were found in all comparisons. CONCLUSIONS: The benefit of WU effect on neuromuscular performance lasts 30 min after FIFA11+ WU activity. Considerations to implement FIFA11+ or conventional dynamic WU exercises for beneficial strategy is warranted.